PENGARUH NON PERFORMING FINANCING (NPF), CAPITAL ADEQUACY RATIO (CAR) DAN INFLASI TERHADAP LIKUIDITAS - Rizka Ardiana Gunawan; Gusganda Suria Manda (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
This study aims to examine the effect of Non Performing Financing (NPF), Capital Adequacy Ratio (CAR), and inflation on liquidity in Islamic banking. This type of research is quantitative research. The population of this study is all Islamic banking companies registered with the financial services authority (OJK). The research sample was selected using purposive sampling method in order to obtain 12 banking companies. The data analysis used multiple linear regression analysis. The results showed that NPF had no effect on FDR, while CAR and inflation had an effect on FDR. In addition, NPF, CAR, and inflation have a significant effect on the level of liquidity (FDR).